"Hablemos de Alzheimer": Words Mexican Americans use to talk about Alzheimer's disease genetic testing. Implications for precision medicine education. (20th December 2022) - Fong, Jamie C; Chavez, Fatima; Silos, Karla; Castro, Gabriela Castro; Arroyo‐Miranda, Mirna L; Kunik, Mark E; Shulman, Joshua M; Medina, Luis D
Abstract: Background: Effective Alzheimer's disease (AD) diagnosis and therapy will require a tailored approach to each person's unique AD manifestation, known as AD precision medicine (PM). PM‐associated comprehensive genetic testing is currently restricted to the research domain and not readily available to minoritized Hispanics/Latinos (H/L). Successful AD precision medicine programs benefitting everyone require culturally appropriate patient outreach/education materials. We investigated the words H/L use to talk about AD genetic testing. Method: We conducted freelisting interviews with 14 Spanish‐preferring Mexican American adults (female, 85.7%; mean age, 49.3±16.8 years, range = 19‐73; completed less than or at most a high school education, 35.7%). Participants were presented with vignettes about a H/L father of varied ages (5 th ‐7 th decade) and degrees of cognitive impairment (no memory deficits to severe memory loss) who received genome sequencing results. During freelisting, participants were given prompts about the vignettes, and were asked to list all words that came to mind when they thought about the prompts. Responses were reviewed for semantically related words. Discrepancies were resolved by consensus agreement. Among sociodemographic data collected, familism and perceived social status were measured by the Pan‐Hispanic Familism Scale and scored (1‐strongly disagree to 5‐strongly agree, max score 25), and the MacArthur Scale of Subjective Social Status (SSS; each item: 1‐lowest to 10‐highest), respectively. Results: Highest frequency unique word/word clusters (n = 151) for one vignette (father: age 70 with cognitive slowing, prompt: father's reaction to his own moderate risk result) included worry (17.2%), age/aging/older (15.9%), family (12.6%), high/medium/low chance (12.6%), Alzheimer's (10.6%), and normal/well/healthy (7.9%). High frequency of family‐related worry aligned with high familism scores (M = 23.2±2.6, range = 15‐25). Moderate frequency words of participants, 78.6% of whom perceived they held social standing in the top half of the community (SSS>5), reflected action orientation: do (6.6%), seek (1.7%), inform (1.5%), and manage (1.1%). Conclusion: Spanish‐preferring Mexican Americans respond robustly to information about family. Family‐centered educational materials about AD precision medicine, including information about healthy aging versus neurodegeneration, risk magnitude categories, and action words, could have high impact. Additional research to learn words used by diverse Spanish‐preferring H/L is needed.